Sleepwalker [compact disc, unabridged] - Robards, Karen (Brilliance Audio, 2011)
While housesitting for her Uncle Nicco, policewoman Micayla Lange catches Jason Davis in the act of stealing money from her uncle's locked safe. But when they both find incriminating photos that implicate Nicco in the murder of a city councilman, Mick and Jason hurtle into a race for their lives.